2019
DOI: 10.1177/1933719118756751
|View full text |Cite
|
Sign up to set email alerts
|

The Essential Role of GATA6 in the Activation of Estrogen Synthesis in Endometriosis

Abstract: Endometriotic stromal cells synthesize estradiol via the steroidogenic pathway. Nuclear receptor subfamily 5, group A, member 1 (NR5A1) is critical, but alone not sufficient, in activating this cascade that involves at least 5 genes. To evaluate whether another transcription factor is required for the activation of this pathway, we examined whether GATA Binding Protein 6 (GATA6) can transform a normal endometrial stromal cell (NoEM) into an endometriotic-like cell by conferring an estrogen-producing phenotype.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 36 publications
0
14
0
3
Order By: Relevance
“…Another TF, STAT4, was also been linked to endometriosis-related infertility by Zamani et al ( 2016 ). In our research, NR5A1 was high expression in the infertile females with endometriosis and it had the ability to transfer an endometrial stromal cell to an endometriotic-like cell with GATA6 simultaneously by the study of Bernardi et al ( 2019 ). In the meantime, ESR2 also exhibited high expression and studies had proved that ESR2 could influence susceptibility to endometriosis with infertility (Lamp et al, 2011 ).…”
Section: Discussionmentioning
confidence: 56%
“…Another TF, STAT4, was also been linked to endometriosis-related infertility by Zamani et al ( 2016 ). In our research, NR5A1 was high expression in the infertile females with endometriosis and it had the ability to transfer an endometrial stromal cell to an endometriotic-like cell with GATA6 simultaneously by the study of Bernardi et al ( 2019 ). In the meantime, ESR2 also exhibited high expression and studies had proved that ESR2 could influence susceptibility to endometriosis with infertility (Lamp et al, 2011 ).…”
Section: Discussionmentioning
confidence: 56%
“… 34 DNMT-3B aberrantly expressed itself inside eutopic endometrial and endometriotic stromal cells during decidualization, linking to genetic areas of the steroidogenic factor 1 ( NR5A ) and estrogen alpha-receptor ( ESR1 ). 35 , 36 Also, abnormal DNA methylation in endometriosis activates the expression of several genes, including homeobox A10 ( HOXA10 ), estrogen beta-receptor gene ( ESR2 ), progesterone receptor (PGR), aromatase ( CYP19A1, HOXC6 , and ALDH1A2) ( Figure 1 ). 23 , 31 , 37 , 38
Figure 1 Schematic representation of epigenetic changes associated with endometriosis.
…”
Section: Resultsmentioning
confidence: 99%
“…A total of 110 target genes of miR-200b-3p were screened, and many of them play important roles in the development of endometriosis. They included FOXP1, GATA6, JUN, and EGFR involved in muscle cell proliferation [25][26][27][28]; NTRK2, ZFPM, and VEGFA involved in angiogenesis [29,30]; and DNMT1, EZH2, FOXP1, VEGFA, ZEB1, and ZEB2 involved in EMT [31,32]. Recent studies found that EMT plays an important role in the occurrence and development of endometriosis [33].…”
Section: Discussionmentioning
confidence: 99%